PERANCANGAN DAN IMPLEMENTASI BOT TELEGRAM UNTUK SISTEM TOPUP GAME DENGAN EXPRESS JS - Sunaryono, Sunaryono; Maulana, Irham; Riyandari, Lutvi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STMIK Widya Utama, 2025)
The rapid advancement of information and communication technology has significantly contributed to the growth of the gaming industry in Indonesia, particularly in the online multiplayer game segment. One notable consequence of this development is the rising demand for fast and efficient in-game top-up services. Topup Gameku, a service provider in this sector, has encountered several challenges, including slow transaction processing and suboptimal system integration. This study aims to design and develop an automated topup system utilizing a Telegram bot to enhance operational efficiency and user experience. The system was developed using the Agile Scrum methodology, allowing for iterative and structured development. Functional testing was conducted using the Black Box Testing method, while user experience was evaluated through the ULEA method involving 40 respondents to assess usability, learnability, efficiency, and acceptability. The evaluation results indicate that the system performed effectively, achieving high scores in usability (97.5%), learnability (95%), efficiency (96.9%), and acceptability (97.56%). These findings demonstrate that the proposed system not only meets user and administrator needs but also offers a practical and efficient solution for managing in-game topup transactions.